Studi Literatur tentang Faktor-Faktor yang Berpengaruh dalam Implementasi Enterprise System pada UKM - Heripracoyo, Sulistyo (Bina Nusantara University, 2013)
Small and Medium Enterprises (SMEs) are one of the pillars of Indonesian economy since they contribute to the national Gross Domestic Product in a large number. This study discusses some of the articles to determine the factors that influence the implementation of enterprise applications systems, business intelligence (BI) and cloud computing. SCM, ERP, CRM are applications that provide the benefits of efficiency and effectiveness to the organization that uses and implements them. SCM, ERP, CRM and Business Intelligence needs to be implemented to SMEs in order to improve their performance to compete efficiently and competitively. In addition, SMEs can try cloud computing services by implementing and integrating those applications, although obstacles may be considerable.